I am pretty sure this goes like this
Rearrange (i) so that x=4y+3-3y
Take (ii) and sub x
it will become 2(4y+3-3y)+4y= 18
Now use what you found for y in (iii) and sub in the (ii or i to get x)
lets take (i) 4y+3=3y+x
from (iii) 4(2)+3=3(2)+x
let me know if that's clear enough
Yes that is thank you so much (:
Calculus - I'm a bit confused about the average equations with integration. I ...
algebra - i need help with these problems (either a solution or how to plug them...
Substitution Method-Plz help - Use the Substitution method to solve the system ...
Algebra - Can someone work this out for me? I'm so confused! Solve the system by...
Algebra Question - I did a problem and used the substitution method and it took ...
math - Solve the system by substitution. 3x-3y=-12,y=-3x-12 i see its the same ...
algebra - Solve by elimination method. 2r-5s=-33 5r+2s=48 Solve by substitution ...
algebra - Here is my question. How do you solve th substitution method in this ...
Algebra - The problem is 9x+4y=-12 x=26-5y Solve by substitution method
algebra - Solve: 0.1p + 2.1 = 4.6p - 1.9 + 0.5p I am getting all confused on how...